Ankle arthroscopy in elite athletes: Outcomes and return to sport - Smoot, J. B.; Lam, P.; Sullivan, M. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
We reviewed the results of ankle arthroscopy in a group of 9 elite athletes (11 ankles) to determine their ability to return to sport and their overall outcome.